Evaluación In vitro de la actividad antimicrobiana de las células estromales mesenquimales de gelatina de Wharton (CEM-GW) (2020)
Antimicrobial resistance is a growing problem in global public health and threatens the prevention and effective treatment of infections. The investigation of alternative strategies point to the generation and use of antimicrobial peptides (AMP) given its broad spectrum of antimicrobial activity. A potential source of (AMP) resides in human mesenchymal stromal cells (MSC). MSC have demonstrated potent therapeutic effects in terms of immunomodulation and multilineage differentiation and are actively involved in tissue control and repair. This work focused on exploring the potential antimicrobial effect of MSC isolated from Wharton's jelly (GW) of the umbilical cord upon experimental infection with bacterial strains Escherichia coli 25922, Klebsiella pneumoniae 43816, Staphylococcus aureus 29213 and Staphylococcus epidermidis 12228. Experimental bacterial infection on CEM-GW triggered important antimicrobial activity whose magnitude depended on the inoculated bacterial strain. This observed antimicrobial effect depended strongly on the presence of human platelet lysate (LPh) in MSC growth media. Importantly, based on characterization of RNA expression and secretion of the AMPs β-defensin-1, Lipocalin-2 and Hepcidin in supernatant, the antimicrobial effect of CEM-GW was significantly associated with increased expression and secretion of AMPs, especially β-defensin-1 and Lipocalin-2. These results provide evidence of the antimicrobial effect that CEM-GW exerts on the bacterial strains used, which depends on the presence of LPh and results in the expression and secretion of AMPs, as a potential mechanism of defense against infection.